Changes of the occupied density of defect states of a-Si:H upon illumination - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1996)
We study the light-induced transient changes of the near surface density of occupied states g(E) of undoped and boron-doped a-Si:H with photomodulated total photoelectron yield spectroscopy. The data show an increase of g(E) upon illumination between 0.35 eV above E F and 0.7 eV below E F (towards the valence band) and a decrease in the region of deep valence-band-tail states. The difference signal depends sublinearly on the laser intensity and reaches a maximum of Δg ≈ 10 17 cm -3 eV -1 at a laser intensity of 30 mW cm -2 (λ=532 nm). Time-resolved measurements reveal rise and decay times of the order of milliseconds. The experimental results are explained quantitatively by a recombination model. In the framework of this model, a range of deep defects around mid-gap energy are singly occupied and neutral at probe-light intensities. Additional illumination with a laser leads to double occupation of these defects and a decrease of the valence-band-tail occupation.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.change